2018
DOI: 10.21475/ajcs.18.12.11.p1489
|View full text |Cite
|
Sign up to set email alerts
|

Peel colour, anthocyanin, TSS content and sensory evaluation of some common fruits: A comparative study

Abstract: The study was conducted to identify the best eating quality of some common fruits in the Malaysian local market. The selected market fruits such as papaya, mango, banana, wax apple (jambu madu) and tomato were collected from local markets located in Besut, Terengganu, Malaysia at different ripening stages. The qualities of these fruits were determined by the peel colour analysis, juice, total soluble solids, anthocyanin and total flavonoid content at different ripening stages. Furthermore, sensory evaluation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
2
1
Order By: Relevance
“…The lower average weight loss in the early harvested fruits might be due to limited metabolic and transpiration rates due to limited maturity of the fruits. Similar trends of TSS levels by maturity stages were reported earlier for common fruits including wax apple (Khandaker et al, 2018).…”
Section: Maturity Stagessupporting
confidence: 87%
“…The lower average weight loss in the early harvested fruits might be due to limited metabolic and transpiration rates due to limited maturity of the fruits. Similar trends of TSS levels by maturity stages were reported earlier for common fruits including wax apple (Khandaker et al, 2018).…”
Section: Maturity Stagessupporting
confidence: 87%
“…Lowest brightness was observed in T8 (1.5 µL L -1 with wrapping) and that was not significantly different from T1 and T5 treatments. The immature fruits may have the highest brightness and the value decrease with the fruit maturation (Khandaker et al, 2018). However, present study revealed that application of 1-MCP with or without wrapping may not have any negative effect on fruit brightness.…”
Section: Fruit Color Brightness (Fc_b)contrasting
confidence: 49%
“…The color of the freeze-dried FPP was measured using a tristimulus portable CR-400 colorimeter (Minolta chromameter CR-400, Osaka, Japan). The spectral software was set at L*, a* and b* mode according to Khandaker, et al [18]. L* is indicative of lightness or brightness, a* indicates chromacity on a green to red axis whereas b* indicates chromacity on a blue to yellow axis.…”
Section: Color Measurement Of Fppmentioning
confidence: 99%